THE EVALUATION OF THE INTERNET USAGE HABITS OF PUBLIC EMPLOYEES IN KASTAMONU - ERSIN KAVI; ORHAN KOCAK (Challenges of the Knowledge Society, 2011)
Changes in the last 10 years in information technology have increased the use of computers and internet. The changes brought about fundamental changes the way we do business and behave in social life from communication and reaching information to daily habits. Effective use of the information technology, which has become the main condition of being competitive at work, has required all employees in public and private sectors to improve themselves in the computer and internet usage. In addition, the public sector also encourages the use of internet via e-government applications. Thus, the computers and internet play a big part in the work of public sector and its employees as well. The usage of computers and the internet in working places not only have changed the way we do business also have changed some ethical rules and issues. They brought some complicated problems for people, organizations and states. Online fraud, carelessness, negligence, viruses, system crashing, broadcasting personal information are among the most well-known ethical problems related to computers and internet and caused by employees. In addition to these, personal use of computers and internet by employees for their private usage during working hours create another problem. The objective of the study is to reveal the internet usage habits and behaviors of public employees at work, using a field research that was carried out in Kastamonu that is a city of north of Turkey. It is especially of interest how and for what purposes the chat programs, which encourage the use of internet, are used. The results are analyzed from the point of view of public ethics. The data is collected from the state servants in Kastamonu and is analyzed on SPSS statistic program.